PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI ERA MERDEKA BELAJAR PADA MASA PANDEMI COVID-19 DI SMA ISLAM ALMAARIF SINGOSARI - Khumairoh Dewi Nur Aini; Maskuri Bakri; Lia Nur Atiqoh Bela Dina (VICRATINA, 2021)
The,study entitled learning religious education in the independent era learning during the covid-19 pandemic at Almaarif Singosari Islamic High School discussed three problem formulations, namely how to plan learning, how to implement learning and how the Islamic religious education learning model was applied during the covid-19 pandemic at Almaarif Islamic High School. Singosari. The method used in this research is a qualitative method using the type of field research. The presence of the researcher is known to his status as a researcher by the subject or informant. The supporting instruments used in this research are observation guidelines, interview guidelines, documentation, and other tools needed in the research process. The results of the study found that there were several plans in learning including curriculum, learning tools, learning media, learning methods and learning resources. and there are two modes of learning, namely offline learning and online learning during the covid-19 pandemic.